KAJIAN SEMIOTIKA SERIAL TELEVISI MR. ROBOT: REPRESENTASI KAPITALISME DENGAN ANALISIS KOMPOSISI SINEMATIK DALAM EPISODE RUNTIME ERROR - Gifari Romadhon (ROLLING, 2022)
This research analyzes the cinematic composition of television series ‘Mr. Robot: Runtime Error Episode’, in which portrays capitalism. In addition, this study proposes to reveal the capitalism issue based on the evolution framework by Yuval Noah Harari. Research data interpreted by semiotics study of The Codes of Television from John Fiske. Along with that, Fiske’s theory used to examine various codes and signs on the sequences, meanwhile, Harari’s framework figured how capitalism works and enlarges survival chance to construct realism in the movie. Furthermore, the writer used a qualitative study by interpreting sorted data to the chosen theory. As a result, various codes and signs of capitalism at the level of reality, representation, and ideology use individualism aspect as an essential foundation to construct realism as well as widening the chance to survive and thrive in the evolution way.